In Vivo and Ex Vivo Patient‐Derived Tumor Xenograft Models of Lymphoma for Drug Discovery. Issue 4 (16th April 2021) - Cacciapuoti, Maria Teresa; Cappelli, Luca Vincenzo; Fiore, Danilo; Toruno, Pedro; Kayembe, Clarisse; Tam, Wayne; Inghirami, Giorgio
Abstract: In the hemato‐oncology field, remarkable scientific progress has been achieved, primarily propelled by the discovery of new technologies, improvement in genomics, and novel in vitro and in vivo models. The establishment of multiple cell line collections and the development of instrumental mouse models enhanced our ability to discover effective therapeutics. However, cancer models that faithfully mimic individual cancers are still imperfect. Patient‐derived tumor xenografts (PDTXs) have emerged as a powerful tool for identifying the mechanisms which drive tumorigenesis and for testing potential therapeutic interventions. The recognition that PDTXs can maintain many of the donor samples' properties enabled the development of new strategies for discovering and implementing therapies. Described in this article are protocols for the generation and characterization of lymphoma PDTXs that may be used as the basis of shared procedures. Universal protocols will foster the model utilization, enable the integration of public and private repositories, and aid in the development of shared platforms. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Tissue handling and cryopreservation of primary and PDTX samples Basic Protocol 2 : Performing tumor implant in immunocompromised mice PDTX models Alternate Protocol 1 : Intra‐medullary femoral injection Alternate Protocol 2 : Intravenous injection Alternate Protocol 3 : Intraperitoneal injection Support Protocol 1 : Phenotypical characterization of PDTXs by flow cytometry Support Protocol 2 : Biological and molecular characterization of PDTX tumors by PCR detection of IGK, IGH, and TCR rearrangements Basic Protocol 3 : Harvesting PDTX‐derived tumor cells for ex vivo experiments Basic Protocol 4 : In vivo testing of multiple compounds in a PDTX mouse model